Strategi Peningkatan Brand Image Melalui Digital Business pada UMKM Ayam Celup Juaro di Kota Medan - Berkat Obed Sion Gultom; Yohanna Dwi Simaremare; Elprina Sihotang; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The development of digital technology has changed the paradigm of MSME businesses, including in building brand image. This study analyzes strategies for enhancing brand image through digital business at Ayam Celup Juaro’s MSMEs in Medan City. The research method uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation studies. The results show that multi-platform digital integration (Instagram, TikTok, WhatsApp) is effective in building brand image. Instagram serves as a medium for visual representation of the brand, TikTok as a driver for acquiring new customers through viral content, and WhatsApp as a means of personal communication to maintain customer loyalty. The key factors for success are content consistency and timely service. The main obstacles faced are budget constraints and challenges in maintaining content consistency. This research provides practical contributions for SMEs in developing integrated digital strategies to enhance brand image in the era of the 4th Industrial Revolution.